Vegetables Importance of Quality Vegetables to Human Health - Asaduzzaman, Md; Asao, Toshiki (IntechOpen, 2018)
The book Vegetables - Importance of Quality Vegetables to Human Health provides useful and interesting information on the nutritional qualities of different vegetables and their roles in disease prevention. Quality vegetable production through hydroponic cultivation techniques is also included. The first few chapters discuss the importance of quality vegetables to human diet and health, and noncommunicable disease prevention. Nutritional qualities and bioactive compounds in freshly grown vegetables through hydroponics and soilless cultures are discussed in the middle part of the book. The final chapter describes methods of sea vegetable utilization in food formulation. This book mainly focuses on the nutritional quality of vegetables and disease prevention, their production methods, preparation, and cooking methods, making it a complete and useful resource to readers.